HTLV-1 ORF-I Encoded Proteins and the Regulation of Host Immune Response: Viral Induced Dysregulation of Intracellular Signaling - Carolina Rosadas; Marzia Puccioni-Sohler (Journal of Immunology Research)
The human T-cell lymphotropic virus type 1 (HTLV-1) is a retrovirus associated with both proliferative and inflammatory disorders. This virus causes a persistent infection, mainly in CD4+ T lymphocyte. The ability to persist in the host is associated with the virus capacity to evade the immune response and to induce infected T-cell proliferation, once the HTLV-1 maintains the infection mainly by clonal expansion of infected cells. There are several evidences that ORF-I encoded proteins, such as p12 and p8, play an important role in this context. The present study will review the molecular mechanisms that HTLV-1 ORF-I encoded proteins have to induce dysregulation of intracellular signaling, in order to escape from immune response and to increase the infected T-cell proliferation rate. The work will also address the impact of ORF-I mutations on the human host and perspectives in this study field.